Flights of fancy - Turano, Jen (American heiresses, 2019)
To escape an unwanted marriage, heiress Isadora Delafield runs away and disguises herself as a housekeeper. She finds a position at the home of self-made man Ian MacKenzies parents. Ian is unexpectedly charmed by Isadora and her unconventional ways, but when Isadoras secret is revealed, will they still have a chance at happy-ever-after?